Pre-Transplant Hypoalbuminemia Is Not Associated With Early Key Outcomes Among Simultaneous Pancreas and Kidney Transplant Recipients - Ekaterina Fedorova; Sofia Nehring Firmino; Dixon B. Kaufman; Jon S. Odorico; David Aufhauser; Carrie Thiessen; David P. Al-Adra; Didier Mandelbrot; Brad C. Astor; Brad C. Astor; Sandesh Parajuli (Transplant International)
The role of pre-transplant hypoalbuminemia and its impact on post-transplant outcomes in patients undergoing simultaneous pancreas-kidney (SPK) transplantation remains unclear. We analyzed all SPK recipients at our center, who had at least 2 weeks of pancreas and kidney graft survival and had serum albumin measured within 45 days pre-transplant. Recipients were categorized based on pretransplant albumin level as normal (≥4.0 g/dL, N = 222, 42%), mild hypoalbuminemia (≥3.5–<4.0 g/dL, N = 190, 36%), and moderate hypoalbuminemia (<3.5 g/dL, N = 120, 23%). Kidney delayed graft function (DGF), length of stay (LOS) after transplant, re-hospitalization within 30 days after discharge, and need for a return to the operating room (OR) related to transplant surgical complications, acute rejection, and uncensored and death-censored graft failure, within the first years post-transplant were outcomes of interest. A total of 532 SPK recipients were included. Mild or moderate hypoalbuminemia was not associated with DGF, LOS, re-hospitalization, or return to the OR in unadjusted or adjusted analyses. Similarly, mild or moderate hypoalbuminemia was not associated with a risk of graft rejection or graft failure. Among SPK recipients, pre-transplant hypoalbuminemia was not associated with worse outcomes and should not be the determining factor in selecting patients for SPK transplant.